BUSINESS STRATEGY ANALYSIS FOR TAHU SARIBUMI RESTAURANT - Khalandara, Khalandara; Wandebori, Harimukti (Journal of Business and Management, 2017)
Abstract. Tahu Saribumi is a tofu restaurant that has been established from 1971 and serves tofu as the main dish. The restaurant located approximately 3 km from the downtown of Sumedang City. Tahu Saribumi considered a senior tofu restaurant with loyal customers since its establishment. Tahu Saribumi restaurant has experienced a decrease in revenue since 2014. The purpose of this paper is to recommend a business strategy for Tahu Saribumi Sumedang in order to stabilize their restaurant financial situation. This paper aim to formulate business strategy using strategic management approach. To do so, this paper try to identify the internal and external environment conditions of the restaurant. Qualitative and quantitative method are implemented using primary and secondary data. Primary data was gained by conducting in-depth interview with restaurant owner, staff, and customers. Secondary data was gained from articles, reports, and websites. The analysis is conducted using SFAS analysis. Result of analysis shows that while Tahu Saribumi is faced with various external opportunity, the business itself still have several major weaknesses that needs to be improved. The recommended suggestion is to create a plan for Tahu Saribumi, consists of short term which is developing new new product development and marketing strategy. Moreover, for long-term plan consisted of human resources, and financial plan.Â Keywords:Â  strategic management, business strategy, tofu restaurant, tofu industry